Evaluación tomográfica de órbitas y su contenido en pacientes con trauma cráneo-encefálico. - Andrade Ortiz, Cristina Nataly. (2014)
The Craneal – Encephalic Trauma,constitutes one of the most important causes that people assist to the Emergency Service. Usually, it is related to collateral damage such as traumatic injuries on facial jaw and ocular orbit should compromise cavity, eyeball, near glandules and soft tissue An important percentage of these patients have to go under Radiology - Image examination. The porpoise of this study is to identify and classify orbital lessons related to Cranial – Encephalic Trauma using Computational Tomography. This is a statics study based on patients that have been attended on Isidro Ayora Emergency Service from October to December on 2013, by performing a systematic analyze oriented to find data, give classification an frequency, in agreement to genre and ethnic group. Every ethnical group and both genres had been included with the only disaggregation of being under 24 hours since the trauma occurred. This study has employ Computer Tomography due to its capabilities of multiplanar reconstruction and 3Dapplications which brings information to diagnose orbital trauma. Radiologist should practice a systematic analyze of the orbital trauma to prevent passing out injuries that may put on risk patient vision.